Альбом - Войнович Владимир (Центр книги Рудомино, 2012)
Экземпляры: Селтинская районная библиотека (аб) (20141110) / Инвентарный номер: 201057 / Цена: 150.00 / Авт.знак: В 61 / ГРНТИ: 17 / ББК: 84(2=411.2)6